Architecture of a sandstone uranium reservoir and the spatial distribution of its internal carbonaceous debris: A case study of the Zhiluo Formation, eastern Ordos Basin, northern China. (15th April 2020) - Tao, Zhenpeng; Jiao, Yangquan; Wu, Liqun; Rong, Hui; Zhang, Fan; Yue, Liang
Graphical abstract: Highlights: Six kinds of architectural elements are identified in the sandstone uranium reservoir. The subaqueous distributary channel formed in four stages: channel-occurring, channel-flooding, channel-waning, channel-abandonment. The carbonaceous debris-rich zones overlie the basal surfaces of intrachannel units and barforms. Abstract: The sandstone of the Middle Jurassic Zhiluo Formation, in the eastern Ordos Basin, provides the opportunity for conducting a critical case-study of the architecture and internal carbonaceous debris (CD) distribution of a sandstone uranium reservoir located in a field outcrop in Shiwan. The 16–24 m thick outcrop section is a sandstone-dominated subaqueous distributary channel succession, in which six lithofacies types (Se, St, Sm, Sp, Sh, and Fl) occur in a predictable order of repeated fining-upward cycles. These facies emphasize that the dominant structures had been deposited under lower flow regime conditions. Various groups of associated facies have been identified as six distinct architectural elements (intrachannel units, longitudinal bar, transverse bar, diagonal bar, dune complex, and abandoned channel deposits) within a framework of five orders of bounding surfaces. These elements, with specific lithofacies associations and spatial relationships, indicate that the subaqueous distributary channel had involved in four stages of formation: channel-occurring, channel-flooding, channel-waning, and channel-abandonment. Moreover, as one of the most significant reductants in the sandstone succession, the CD occurs in the form of channel lags and is concentrated in the middle and lower parts of the lag deposit zones. The spatial distribution of CD within the studied succession is controlled by the sandstone architecture and the CD-rich zones are preserved exclusively upon the basal surfaces of intrachannel units, longitudinal and transverse bars. This study can be helpful for exploring the distribution of metallogenic flow field as well as the restriction of the reductants on interlayer oxidation.